Efisiensi Fiskal dan Dampaknya terhadap Transfer Dana Daerah: Analisis Kebijakan Inpres No. 1 Tahun 2025 - Ulfiah Syukri; Sofiaturrohmah, Siti; Kasman, Andi (Journal of Governance Innovation, 2025)
Fiscal efficiency plays a crucial role in addressing interregional disparities in Indonesia through the management of fund transfers. This article aims to analyze the impact of Presidential Instruction No. 1 of 2025 on fiscal efficiency and regional fund transfer patterns. The research employs a qualitative methodology utilizing secondary data analysis from official sources and academic studies gathered between March and April 2025. The findings indicate that the implementation of this policy enhances the efficiency of fund transfer usage; however, it also presents challenges such as regional dependency on central transfers and disparities in fiscal capacity. The discussion reveals that while transfer funds can stimulate economic growth, their effectiveness largely depends on sound management at the regional level, which is expected to optimally utilize funds for local development. This study recommends that improving coordination between central and regional governments, along with enhancing local fiscal management capacity, is essential for the successful execution of this policy. In conclusion, to achieve equitable and sustainable fiscal decentralization goals, more integrated efforts are needed in designing policies that consider local conditions and encourage innovation in regional revenue, thereby minimizing fiscal disparities and maintaining economic growth.